Efficacy of bupropion in the indigenous Maori population in New Zealand. Issue 2 (28th January 2005) - Holt, S; Timu-Parata, C; Ryder-Lewis, S; Weatherall, M; Beasley, R
Abstract : Background: Smoking rates are high in indigenous populations and contribute to their poor health. In New Zealand the indigenous Maori population has a high rate of smoking, with around 50% of adults being smokers compared with 20% of the adult European population. A study was undertaken to determine whether bupropion is effective in the treatment of smoking cessation in the indigenous Maori population in New Zealand. Methods: A randomised, placebo controlled, double blind, parallel group study was performed in 134 Maori smokers aged 16–70 years who smoked more than 10 cigarettes per day. The main outcome measures were continued abstinence from smoking at 3 and 12 months. Results: At each time point continued abstinence was better for the subjects allocated to bupropion, with a risk ratio for abstinence over all time points of 2.44 (95% CI 1.22 to 4.88). The rates of continued abstinence in the bupropion and placebo groups at 3 months were 44.3% and 17.4%, respectively, with a risk ratio of 2.54 (95% CI 1.30 to 5.00). The corresponding figures at 12 months were 21.6% and 10.9%, respectively, with a risk ratio of 1.99 (95% CI 0.79 to 5.00). Conclusion: Bupropion is an effective treatment for smoking cessation in the indigenous Maori population in New Zealand.